210Po concentration in selected diatoms and dinoflagellates in the northern Arabian Gulf. Issue 1 (April 2018) - Uddin, S.; Behbehani, M.; Al-Ghadban, A.N.; Sajid, S.; Vinod Kumar, V.; Al-Musallam, L.; Al-Zekri, W.; Ali, M.; Al-Julathi, S.; Al-Murad, M.; Alam, F.
Abstract: Marine phytoplankton is a primary producer in the ocean that forms the base of the marine food web and supports the pelagic food chain. The two dominant groups of phytoplankton observed in northern Gulf waters are diatoms and dinoflagellates. The diatoms outnumber dinoflagellates in the Gulf waters. This study presents baseline information on the concentration of 210 Po among selected phytoplankton in the northern Gulf. The concentration among diatoms varies between 6.99 and 11.4 Bq kg −1 wwt, whereas a higher concentration range of 8.51–15.41 Bq kg −1 wwt was observed among dinoflagellates. The diatoms analyzed includes Thalassiosira spp. – 10.2–11.4 Bq kg −1 wwt; Chaetoceros spp. – 6.99–7.14 Bq kg −1 wwt; Rhizosolenia spp. – 9.12–9.95 Bq kg −1 wwt. The analyzed dinoflagellate genera include Gymnodinium spp. – 8.51–8.78 Bq kg −1 wwt; Noctiluca spp. – 15.2–15.4 Bq kg −1 wwt; and Karenia spp. – 14.1–14.9 Bq kg −1 wwt. The 210 Po concentration in seawater shows a seasonal variation, with a higher concentration range of 0.70 and 0.58 mBq L −1 during summer and autumn, whereas a lower range in concentration of 0.38 and 0.30 mBq L −1 occurring during winter and spring. The resultant computed concentration factors vary between 2 ∗ 10 4 –5 ∗ 10 4 demonstrating a significant 210 Po enrichment in the base of the pelagic food chain. Highlights: This is the first baseline for 210 Po in phytoplankton from northern Gulf. 210 Po concentration in dinoflagellates is higher than diatoms. The concentration factor varies between 1.8 and 5.1 ∗ 10 4 . The study provides a more realistic basis for reference CF value for phytoplankton.